Мент: [роман] / А. Константинов, А. Новиков - Константинов Андрей Дмитриевич (Русский проект, 2000)
Экземпляры: АБ (20190220) / Инвентарный номер: 34300 / Цена: 35.50 / Сис.шифр: 84(2Рос6) / Авт.знак: К 65 / ББК: 84(2Рос6)